True gender ratios and stereotype rating norms - Garnham, Alan; Doehren, Sam; Gygax, Pascal (Frontiers in Psychology, 2015)
We present a study comparing, in English, perceived distributions of men and women in 422 named occupations with actual real world distributions. The first set of data was obtained from previous a large-scale norming study, whereas the second set was mostly drawn from UK governmental sources. In total, real world ratios for 290 occupations were obtained for our perceive vs. real world comparison, of which 205 were deemed to be unproblematic. The means for the two sources were similar and the correlation between them was high, suggesting that people are generally accurate at judging real gender ratios, though there were some notable exceptions. Beside this correlation, some interesting patterns emerged from the two sources, suggesting some response strategies when people complete norming studies. We discuss these patterns in terms of the way real world data might complement norming studies in determining gender stereotypicality.